2022
DOI: 10.3390/cells11152349
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 Channel Activation Reverses Pulmonary Artery Vasoconstriction in an Early Rat Model of Pulmonary Hypertension: The Role of Ca2+ Influx and Akt-eNOS Pathway

Abstract: In intrapulmonary arteries (IPAs), mechanical forces due to blood flow control vessel tone, and these forces change during pulmonary hypertension (PH). Piezo1, a stretch-activated calcium channel, is a sensor of mechanical stress present in both endothelial cells (ECs) and smooth muscle cells (SMCs). The present study investigated the role of Piezo1 on IPA in the chronic hypoxia model of PH. Rats were raised in chronically hypoxic conditions for 1 (1W-CH, early stage) or 3 weeks (3W-CH, late-stage) of PH or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This suggests that other mechanoreceptors are responsible for flow mediated vasodilation in the pulmonary circulation. In support of this, evidence has been presented more recently that Piezo1 channels activate flow mediated vasodilatation in the pulmonary circulation (Lhomme, Gilbert et al 2019, Porto Ribeiro, Barbeau et al 2022).…”
Section: Discussionmentioning
confidence: 83%
“…This suggests that other mechanoreceptors are responsible for flow mediated vasodilation in the pulmonary circulation. In support of this, evidence has been presented more recently that Piezo1 channels activate flow mediated vasodilatation in the pulmonary circulation (Lhomme, Gilbert et al 2019, Porto Ribeiro, Barbeau et al 2022).…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies reported the blockade of piezo1 by ruthenium red and gadolinium [ 19 , 20 , 21 ]. When cells were exposed to Yoda1 in the presence of 50 µM ruthenium red, the Yoda1-induced increased Rb uptake response was abolished ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PIEZO1 is upregulated in pulmonary arterial ECs during pulmonary hypertension, 76 and pharmacological manipulation of its activity has been reported to modulate vascular defects induced in models of vascular calcification, 77 hyperglycemia, 78 and pulmonary hypertension. 79 Moreover, PIEZO1 is directly involved in atherosclerosis, 54 a common condition corresponding to a slowly worsening chronic inflammatory disease (Figure 3B). Atherosclerosis occurs preferentially in branches and curves in arteries exposed to disturbed blood flow inducing inflammation, endothelialmesenchymal transition, thrombosis, vasoconstriction, and barrier dysfunction.…”
Section: Pathogenic Effects Of Endothelial Piezo1 Activity Under Dist...mentioning
confidence: 99%